HCI International 2015 -- Posters' extended abstracts. International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015. Proceedings /: International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015. Proceedings. Part II : (2015) - Unknown
No abstract available